Determination of Traps' Density of State in OLEDs from Current–Voltage Analysis - Zaini, M.S.; Sarjidan, M.A.M.; Majid, W.H.A. (Institute of Physics, 2016)
A simple method to determine the traps density of state (DOS) in organic light-emitting diodes (OLEDs) by manipulating the current-voltage (I-V ) characteristic of the devices at room temperature is introduced. In particular, the trap-dependent space-charge limited current formula is simplified to obtain effective density of traps. In this study, poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(benzo[2,1,3]thiadiazol-4,8-diyl)] (F8BT) and 2- Methoxy-5-(37dimethyloctyloxy) benzene-1,4-diacetonitrile (OC1C10-PPV) are selected as the OLEDs emissive layer. The trap DOS of F8BT- and OC1C10-PPV-based OLEDs are calculated in the magnitudes of 1024 m-3 and 1023 m-3, respectively. In addition, the results agree with the other conventional method which is used to determine the trap DOS in OLEDs. This calculation technique may serve as a robust and reliable approach to obtain the trap DOS in OLEDs at room temperature.